2021
DOI: 10.1515/cclm-2021-0467
|View full text |Cite
|
Sign up to set email alerts
|

The utility of competency-oriented clinical laboratory teaching combined with case-based learning (CBL)

Abstract: Objectives This study aimed to evaluate the effectiveness and efficiency of competency-oriented clinical laboratory teaching combined with case-based learning (CBL) and improve the examination of students’ competence of laboratory medicine. Methods A total of 107 medical laboratory medicine interns at the Affiliated Hospital of Xuzhou Medical University from June 2017 to July 2019 volunteered to participate in the study and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The training mostly adopts group lectures, operation demonstrations, business visits, and difficult case discussions. This is training and assessment implemented from the holistic level of the orthopaedic education profession, which is a common clinical approach [ 29 – 32 ]. With the development of holistic nursing, responsible nursing, high-quality nursing, and evidence-based nursing, as well as the arrival of the era of precision medicine, the precise training of core competencies in specialist nursing is particularly urgent.…”
Section: Discussionmentioning
confidence: 99%
“…The training mostly adopts group lectures, operation demonstrations, business visits, and difficult case discussions. This is training and assessment implemented from the holistic level of the orthopaedic education profession, which is a common clinical approach [ 29 – 32 ]. With the development of holistic nursing, responsible nursing, high-quality nursing, and evidence-based nursing, as well as the arrival of the era of precision medicine, the precise training of core competencies in specialist nursing is particularly urgent.…”
Section: Discussionmentioning
confidence: 99%
“…The CBL method focuses on improving students' competence in laboratory medicine. [14] found that among 107 medical laboratory medicine intern volunteers, in the control group of teacher-centered methods, students in the CBL teaching program had significantly higher theory test scores and skill assessment scores on average. Noticeable improvements included recognizing and processing instrument alarm messages, analyzing test results, identifying and resolving problems, and…”
Section: Teaching Of Problem-based Learning (Pbl) and Case-based Lear...mentioning
confidence: 97%
“…The CBL method focuses on improving students' competence in laboratory medicine. Li et al [14] found that among 107 medical laboratory medicine intern volunteers, in the control group of teacher-centered methods, students in the CBL teaching program had significantly higher theory test scores and skill assessment scores on average. Noticeable improvements included recognizing and processing instrument alarm messages, analyzing test results, identifying and resolving problems, and identifying and reporting critical values and clinical communications.…”
Section: Teaching Of Problem-based Learning (Pbl) and Case-based Lear...mentioning
confidence: 99%